Analyzing Student’s Science Identity in Science Learning: A Survey Research - Maula, Alnafa I’anatul; Winarno, Nanang; Andi, Herman Jufri; Kusumawati, Erna Risfaula (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
The exploration of students’ science identity in Indonesian junior high schools is limited. However, science identity is a crucial factor in influencing students’ decision to pursue a career in science. This study aims to analyze students’ science identity in science learning, specifically focusing on gender differences. The survey method was used, and an instrument was adopted to measure science identity in science learning among junior high school students, utilizing a 5-point Likert scale. The questionnaire consisted of a total of 26 items, including 6 in science performance, 6 in competence, 6 in recognition scales, 6 in interest scales, and 2 open-ended questions. The research sample included 1092 junior high school students from West and East Java, Indonesia. The results revealed that there were no significant differences in the mean science identity between male and female students. However, females had slightly higher averages in science performance and competence, while males had higher recognition scores. This research contributes to the development of science identity, aiming to enhance students’ learning outcomes and future careers in science. It emphasizes that science is a field that is open to both genders.